An experimental study of PV/T system using parabolic reflectors and heat exchanger - Benlaria Ismail; Belhadj Mohammed; Othmane Abdelkhalek; Sabouni Elhadj (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Photovoltaic (PV) systems can be made more efficient by forcing the PV panel to operate at its maximum point power due to the electrical properties of photovoltaic generators, which are substantially non-linear (MPP). This study examines the effectiveness of using a combination of parabolic concentrator Bi-reflector and heat exchanger as a cooling system on the performance of photovoltaic generators to get a photovoltaic/thermal (PV/T) system, and their effect on the direct current (DCDC) converter using matrix laboratory (MATLAB) simulink. The experimental tests were carried out under various temperature values and sun irradiation. The results demonstrated that the use of parabolic Bi-reflectors, to further illumine te the panels, and the use of the cooling system to absorb excess heat to get heat water, could increase and enhances performances of the photovoltaic generator.